De Jules et Jim au Vel’ d’Hiv - Annie Oliver (Cahiers de Narratologie)
In his novel On ne peut plus dormir tranquille quand on a une fois ouvert les yeux Robert Bober draws his inspiration from his own life and tells a good number of events which have really taken place. Starting with the shooting, in 1961, of François Truffaut Jules et Jim. From this movie, as well as from many other film references – from Max Ophuls to the Marx Brothers – the narrator of Jewish-Polish origin rediscovers the history of his own family together with that of Paris, from the 1971 Commune to the 1942 round-up of Jews in the Vélodrome d’Hiver.